Diagnosis and management of Lynch syndrome. Issue Volume 13:Issue e1(2022) (2nd June 2022) - Edwards, Penelope; Monahan, Kevin J
Abstract : Lynch syndrome (LS) is a dominantly inherited cancer susceptibility syndrome defined by presence of pathogenic variants in DNA mismatch repair genes MLH1, MSH2, MSH6 and PMS2, or in deletions of the EPCAM gene. Although LS is present in about 1 in 400 people in the UK, it estimated that only 5% of people with this condition are aware of the diagnosis. Therefore, testing for LS in all new diagnoses of colorectal or endometrial cancers is now recommended in the UK, and gastroenterologists can offer 'mainstreamed' genetic testing for LS to patients with cancer. Because LS results in a high lifetime risk of colorectal, endometrial, gastric, ovarian, hepatobiliary, brain and other cancers, the lifelong care of affected individuals and their families requires a coordinated multidisciplinary approach. Interventions such as high-quality 2-yearly colonoscopy, prophylactic gynaecological surgery, and aspirin are proven to prevent and facilitate early diagnosis and prevention of cancers in this population, and improve patient outcomes. Recently, an appreciation of the mechanism of carcinogenesis in LS-associated cancers has contributed to the development of novel therapeutic and diagnostic approaches, with a gene-specific approach to disease management, with potential cancer-preventing vaccines in development. An adaptive approach to surgical or oncological management of LS-related cancers may be considered, including an important role for novel checkpoint inhibitor immunotherapy in locally advanced or metastatic disease. Therefore, a personalised approach to lifelong gene-specific management for people with LS provides many opportunities for cancer prevention and treatment which we outline in this review.